2004
DOI: 10.1007/s10147-004-0470-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of malignant tumors of the foot and ankle

Abstract: Wide resection of malignant tumors of the foot and ankle is considered technically difficult because of technical problems of soft-tissue coverage. However, utilization of local and free flaps provides sufficient closure following wide tumor resection of the foot and ankle, thus yielding satisfactory lower extremity function and local tumor control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…In both studies, the most frequent histologic type was synoviosarcoma. In relation to multimodality treatment, the review by Ozger et al (13) showed that 88% underwent limb salvage surgery, in most patients, the margins were wide, 81% received chemotherapy, and 69% received radiotherapy. In our study, more patients underwent amputation (44%), in most cases, wide or radical margins were obtained, and fewer patients received chemotherapy (62%) and radiotherapy (26%).…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the most frequent histologic type was synoviosarcoma. In relation to multimodality treatment, the review by Ozger et al (13) showed that 88% underwent limb salvage surgery, in most patients, the margins were wide, 81% received chemotherapy, and 69% received radiotherapy. In our study, more patients underwent amputation (44%), in most cases, wide or radical margins were obtained, and fewer patients received chemotherapy (62%) and radiotherapy (26%).…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7,14,15,19,20 Additionally, few reports did not describe the oncologic outcomes of STS of the foot. 6 So, it is difficult to compare the studies and describe the prognostic factors and to get optimal therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…Limb salvage surgery with pre or postoperative radiotherapy was performed to 6 patients and distant metastasis was detected in one patient after a mean 74.2 months of follow-up. 15 The studies that evaluated the long-term outcomes of patients treated with limb sparing surgery and radiotherapy for STS of the foot demonstrated an excellent rates of local control and survival with good functional outcome (Table 4). [16][17][18] However, in Jyothirmayi et al's series local relapse-free survival was high as 44%, compared to other studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations